1988
DOI: 10.1515/cclm.1988.26.1.7
|View full text |Cite
|
Sign up to set email alerts
|

The Distribution of Unsulphated and Sulphated Glycosaminoglycans in Palmar Fascia from Patients with Dupuytren’s Disease and Healthy Subjects

Abstract: Eighty specimens from 20 patients with Dupuytren's disease and 7 biopsies of healthy palmar fascia were analysed for their glycosaminoglycan isomer patterns with a combined enzymatic/HPLC method. The diseased portions of palmar fascia tissue were characterized by elevated total glycosaminoglycans together with a relative increase in the sulphated fractions. The macroscopic stages of nodules, bands and unaffected tissue could be classified very well by multivariate statistical analysis on the basis of their gly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

1993
1993
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 10 publications
2
4
0
Order By: Relevance
“…Connected with Dupuytren's contracture, the alterations in matrix PGs lead to an accumulation of DS and CS in diseased tissue. This latter phenomenon has been reported by others (33,34). It is worthy of note that similar remodeling of the matrix PG (and matrix GAG) profile has been observed in the case of hypertrophic skin scars (35) and scarred fascia lata (15), demonstrating the existence of common mechanisms involved in some types of wound healing and Dupuytren's disease.…”
Section: Downloaded Fromsupporting
confidence: 84%
“…Connected with Dupuytren's contracture, the alterations in matrix PGs lead to an accumulation of DS and CS in diseased tissue. This latter phenomenon has been reported by others (33,34). It is worthy of note that similar remodeling of the matrix PG (and matrix GAG) profile has been observed in the case of hypertrophic skin scars (35) and scarred fascia lata (15), demonstrating the existence of common mechanisms involved in some types of wound healing and Dupuytren's disease.…”
Section: Downloaded Fromsupporting
confidence: 84%
“…tion II DS in relation to fraction I GAG found in DF as compared to normal tissue. Moreover, our suggestion concerning the oversulfation of DF derived DS is confirmed by the results of Tunn et al (1988), who found increased content of sulfated disaccharides generated by chondroitinase ABC action on the GAG from such tissue samples. The profound remodeling of DS profile also involving an increase in this GAG content, observed by us in advanced DC, may be due to two reasons: (i) alterations in expression of particular DSPGs manifested most probably by enhanced biosynthesis of small leucine rich PG biglycan (Koźma et al, 2005) as well as (ii) changes in activity of GAG modifying enzymes.…”
Section: Discussionsupporting
confidence: 84%
“…On the other hand, as it has been revealed in in vitro studies, these molecules influence glycosaminoglycan metabolism also affecting DS structure (Kinsella et al, 2004;Tiedemann et al, 2005). Indeed, an accumulation of DS and chondroitin sulfate (CS) is observed in Dupuytren's fascia (Flint et al, 1982;Tunn et al, 1988). However, the detailed aspects of disease-associated metabolism of DS as the major GAG both of normal and Dupuytren's fascia ECM (Flint et al, 1982) is poorly known.…”
Section: Introductionmentioning
confidence: 99%
“…The increase in collagen denaturation temperature observed in palmar aponeuroses from patients with NIDDM is the consequence of increased cross-linking due to NEG. On the other hand, in DC several biochemical changes have been described: (1) increase in the relative proportion of type III collagen (Bailey et al, 1977), (2) increased proteoglycan content relative to collagen (Tunn et al, 1988), (3) a lysyl-overmodification of collagen type I (Bailey et al, 1977), and (4) fewer cross-links than found in normal palmar aponeuroses (Bailey, 1994). Of these changes, the third and the fourth explain the reduction in collagen denaturation temperature which was already described by Nemetschek et al (1976).…”
Section: Discussionmentioning
confidence: 99%